Acute lymphoblastic leukemia: age and biology - Foà, Robin (PAGEPress Publications, 2011)
Acute lymphoblastic leukemia (ALL) is the most frequent neoplasm in children, while being relatively rare in adults. The outcome of children with ALL is far superior than that observed in adults, whose survival rates generally do not exceed 40%. A retrospective analysis recently carried out on a large series of cases enrolled in the AIEOP and GIMEMA protocols for the treatment of pediatric and adult ALL has documented specific differences among the various age cohorts examined, particularly in terms of incidence of molecular rearrangements, with the BCR/ABL rearrangement being detected in more than half of patients in the 6(th) decade of life. These findings highlight the importance of a precise diagnostic screening at all ages, since elderly patients might benefit more from targeted approaches, that are associated with less toxic effects. Furthermore, extended biologic approaches aimed at identifying novel therapeutic targets should be regarded as a main goal to refine our therapeutic armamentarium. Finally, the introduction of pediatric-like protocols is progressively changing the outcome of young adult patients, although an important caveat is represented by the comorbidities and toxic effects associated with more aggressive chemotherapy; therefore, patients' fitness should always be carefully considered.